ELEMENTARY SCHOOL STUDENTS' DIGITAL LITERACY READINESS FOR SOCIAL MEDIA AND DIGITAL INFORMATION - Ardis, Nurfaidah; Abdullah, Abid Raisardhi (Program Studi Bimbingan dan Konseling FKIP UNJA, 2026)
This study aims to determine the digital literacy readiness of elementary school students in Makassar City for social media and digital information. The study used a quantitative approach with descriptive methods. The study subjects were 223 fifth and sixth grade elementary school students in Makassar City. Data collection was conducted using a six-item Guttman scale questionnaire. Data analysis was conducted using descriptive statistics, including mean, median, standard deviation, percentage, and categorization of students' digital literacy readiness levels. The results showed that students' digital literacy readiness was in the high category, with a percentage of 81.2%. Most students understood the basics of cyberbullying, social media use, and the importance of being cautious about digital information and fake news on the internet. Furthermore, the majority of students had social media accounts such as WhatsApp, TikTok, YouTube, and Instagram. However, some students still had low levels of digital literacy readiness, requiring strengthening digital literacy education through the role of schools and parents to enable students to use social media and digital information safely and responsibly. Keywords: digital literacy, social media, elementary school students, digital information